Misinterpretation of "Compliance" in Village Planning and Budgeting - Moh Toyyib; Bambang Haryadi; Rita Yuliana (JAFFA, 2023)
This study aims to explore the erroneous interpretation of compliance culture in planning and budgeting practices within the Madurese cultural frame. This study uses a qualitative method with an ethnographic approach. They are collecting data through interviews, observations, and documentation studies. The researcher's findings are that obedience to the leader is a tradition of the ancestral Madurese people, which is contained in the sayings Bhupa', bhabu, ghuru, and rato—blind obedience or loyalty without seeing right and wrong leads to deviant behavior. The philosophy of the Madurese tradition and Islamic teachings teach obedience or noro 'bunte' to parental leaders only in the context of goodness. If the leader commits a wrong action, then a subordinate is obliged to remind him